Isolation and characterization of friedelin and 5-dodecylresorcinol from the stem bark extract of Pterocarpus erinaceus - Ibrahim, Marwan (Tanjong Malim, 2022)
Isolation and characterization of friedelin and 5-dodecylresorcinol from the stem bark extract of Pterocarpus erinaceus by Ibrahim, Marwan